Pengembangan Kawasan Wisata Tsunami di Kota Banda Aceh (Studi Implementasi Kebijakan Qanun Aceh Nomor 8 Tahun 2013 Tentang Kepariwisataan) - Muhammad Munzir; muhammad Zainal Abidin; Faridah; Kamal Fachrurrozi; Fadli Syahputra (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2022)
This research is important because until now the local revenue of Kota Banda Aceh from tourism is still low, whereas there are still many tourism potentials that can still be dug for, if there is tourism activity is not lively and not festive and generally not maintained, including supporting facilities for such activities not well maintained. Many debates about tourism post disaster. During this time the disaster is considered a threat, but the facts on the ground show that many people are interested to see and enjoy the impact of the Tsunami disaster. The formulation of the problem in this research is how to arrange / facilitate the development of tourist attraction in Banda Aceh City, how to organize tourism training, how to maintain and preserve the tourist attraction in Banda Aceh City, how to organize guidance of the conscious society of tourism in Banda Aceh City, how to do promotion tour. This research uses qualitative approach. Because the researchers intend to get a picture of a profound phenomenon about a symptom. Technique of data collecting is by interview, observation and documentation study. the data source consists of primary data source and secondary data source. In conducting research of informant search done by purposive sampling technique. The informant consisted of the Head of the Tourism Office of Banda Aceh City, Secretary of Tourism Office, Kabid. Tourism, Sub-Head of Planning, Head of Marketing and Development Section, Owner of Hotel Arabia, Sub-district of Meuraxa, Public figure, Tourist owner Iboh, Hotel Owner of Tourism, Business Owner of Floating Ship Object. From the results of the research shows that the development of tourist attraction continues in galakkan by the city of Banda Aceh, the implementation of tourism training followed by the entrepreneurs and the community around the tourist attraction. Maintenance and preservation of tourist attraction in do not meet the expectations of visitors, the guidance of the community aware of tourism in greet the community is less serious, the promotion is not so vigorous and attract many tourists. From the result of the research, it can be concluded that the development of tsunami tourism area in Banda Aceh City still needs improvement and the government's attention for further development.